Development and Validation for Determination of Apremilast in Bulk and in Tablets by UV Spectrophotometer (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Pharmaceutical analysis plays a key role in the quality assurance and quality control of bulk drugs.A documented validation program offers a high level of confidence that an operation or facility will consistentlydeliver a product that satisfies a set standard. A premilast is an aphosphodiesterase-4 inhibitor used in thetreatment of psoriasis. Objective: The main objective is to develop a simple, rapid, accurate, and economicalspectrophotometric method for the determination of apremilast in bulk and its tablet dosage form as per ICHguidelines. Materials and Method: The estimation was carried out using HPLC-grade acetonitrile as a solventand quantitation was achieved using a double-beam UV spectrophotometer at 230 nm. The present method wassuitable for its intended purpose as prescribed in ICH Q2 guidelines. The analytical method was validated todetermine the linearity, precision, accuracy, robustness, ruggedness, LOD, and LOQ of the method. Results: Theλmax of apremilast in acetonitrile was found to be 230 nm. The drug has a correlation coefficient (r2) value of0.999 and exhibits linearity in the concentration range of 2–10 μg/mL. The proposed method was applied topharmaceutical formulation and % the amount of drug estimated 99% was found in good agreement with the labelclaim. The repeatability, intraday, and interday changes of accuracy were examined. The approach is consideredexact if the percentage RSD value is